(untitled) (Journal of Hama University, 2022)
Anxiety is one of the most important emotions facing the athlete in sports competitions, which affects his performance and achievement, especially in individual competitive sports such as athletics. The aim of this research is to identify the level of anxiety and its relationship to the digital achievement of athletics players. In this study, the descriptive approach was used in the style of associative relations for its relevance to the nature of this research, and the sample included a group of athletics players in the Syrian Arab Republic (Lattakia city) for the 2019-2020 sports season, which numbered (23) male and female track and field athletes. And to find out the correlation between the level of anxiety and the digital achievement of the sample members, the arithmetic mean and the Pearson correlation coefficient were used. The results showed the presence of a medium level of anxiety among the studied sample and the absence of a significant correlation between the variables of the level of anxiety and the level of digital achievement during training and competition.